A polyamidoamine-mediated competitive colorimetric assay based on gold nanoparticles for determining acid values in edible sunflower seed, corn and extra virgin olive oils. (1st July 2019) - Guo, Yujun; Liang, Xiao; Bi, Junmin; Ling, Rui; Jiang, Yuhao; Mou, Zhoufan; Huang, Feng; Qin, Weidong
Highlights: Polyamidoamine generation 1.0 triggers aggregation of gold nanoparticles. Fatty acids disassemble the polyamidoamine/nanoparticle aggregates. The aggregation/disassembling process is reflected by changes in UV–Vis spectra. The spectroscopy is employed in determining total free fatty acids in edible oils. Abstract: We synthesized polyamidoamine (PAMAM) dendrimers and citrate-capped gold nanoparticles (AuNPs), and explored the applicability of the PAMAM/AuNP assay in determining total free fatty acid (FFA) contents in edible oils based on a competitive colorimetry, in which the PAMAM-triggered AuNP aggregation was suppressed by FFAs. The generation and concentration of PAMAMs, the chain lengths of FFAs as well as the concentration and pH of the background electrolytes of the assay were optimized. The average acid values of the sunflower seed, corn and extra virgin olive oils determined by PAMAM/AuNP assay were 1.31 ± 0.07, 0.33 ± 0.02 and 1.49 ± 0.07, respectively, which were not significantly different from the corresponding 1.27 ± 0.08, 0.32 ± 0.01 and 1.61 ± 0.06 by the standard nonaqueous titration. Our results suggest that the method is promising in detecting FFAs in edible oils, and implementation of the method expands the technological scope for FFA analysis.